Paths to Victory Detailed Insurgency Case Studies - Paul, Christopher (RAND Corporation, 2013)
In-depth case studies of 41 insurgencies since World War II break each conflict into phases and examine the trajectory that led to the outcome (insurgent win or counterinsurgent win). Detailed analysis of the findings, including those from an original set of 30 insurgencies (for a total of 71 historical cases), is available in the companion volume, Paths to Victory: Lessons from Modern Insurgencies.